Differential role of the menthol-binding residue Y745 in the antagonism of thermally gated TRPM8 channels - Malkia, Annika (BioMed Central, 2009)
BACKGROUND: TRPM8 is a non-selective cation channel that belongs to the melastatin subfamily of the transient receptor potential (TRP) ion channels. TRPM8 is activated by voltage, cold and cooling compounds such as menthol. Despite its essential role for cold temperature sensing in mammals, the pharmacology of TRPM8 is still in its infancy. Recently, tyrosine 745 (Y745) was identified as a critical residue for menthol sensitivity of the channel. In this report, we study the effect of mutating this residue on the action of several known TRPM8 antagonists: BCTC, capsazepine, SKF96365, and clotrimazole as well as two new inhibitor candidates, econazole and imidazole. RESULTS: We show that Y745 at the menthol binding site is critical for inhibition mediated by SKF96365 of cold- and voltage-activated TRPM8 currents. In contrast, the inhibition by other antagonists was unaffected by the mutation (BCTC) or only partially reduced (capsazepine, clotrimazole, econazole), suggesting that additional binding sites exist on the TRPM8 channel from where the inhibitors exert their negative modulation. Indeed, a molecular docking model implies that menthol and SKF96365 interact readily with Y745, while BCTC is unable to bind to this residue. CONCLUSION: In summary, we identify structural elements on the TRPM8 channel that are critical for the action of channel antagonists, providing valuable information for the future design of new, specific modulator compounds.